Cardiac risk assessment with the Revised Cardiac Risk Index index before elective non-cardiac surgery: A retrospective audit from an Australian tertiary hospital. Issue 6 (November 2021) - Yao, Yao; Dharmalingam, Ashok; Tang, Cyril; Bell, Harrison; DJ McKeown, Andrew; McGee, Michael; Davies, Allan; Tay, Tracey; Collins, Nicholas
: Clinicians assessing cardiac risk as part of a comprehensive consultation before surgery can use an expanding set of tools, including predictive risk calculators, cardiac stress tests and measuring serum natriuretic peptides. The optimal assessment strategy is unclear, with conflicting international guidelines. We investigated the prognostic accuracy of the Revised Cardiac Risk Index for risk stratification and cardiac outcomes in patients undergoing elective non-cardiac surgery in a contemporary Australian cohort. : We audited the records for 1465 consecutive patients 45 years and older presenting to the perioperative clinic for elective non-cardiac surgery in our tertiary hospital. We calculated individual Revised Cardiac Risk Index scores and documented any use of preoperative cardiac tests. The primary outcome was any major adverse cardiac events within 30 days of surgery, including myocardial infarction, pulmonary oedema, complete heart block or cardiac death. : Myocardial perfusion imaging was the most common preoperative stress test (4.2%, 61/1465). There was no routine investigation of natriuretic peptide levels for cardiac risk assessment before surgery. Major adverse cardiac events occurred in 1.3% (18/1366) of patients who had surgery. The Revised Cardiac Risk Index score had modest prognostic accuracy for major cardiac complications, area under receiver operator curve 0.73, 95% confidence interval 0.60 to 0.86. Stratifying major adverse cardiac events by the Revised Cardiac Risk Index scores 0, 1, 2 and 3 or greater corresponded to event rates of 0.6% (4/683), 0.8% (4/488), 4.1% (6/145) and 8.0% (4/50), respectively. : The Revised Cardiac Risk Index had only modest predictive value in our single-centre experience. Patients with a revised cardiac risk index score of 2 or more had an elevated risk of early cardiac complications after elective non-cardiac surgery.